QUALITY OF LIFE AT WORK OF EARLY CHILDHOOD EDUCATION TEACHERS IN A MUNICIPALITY ON THE COAST OF THE STATE OF PARANÁ - França, Denise Maria Vaz Romano; Simões, Pierangela Nota (Seven Editora, 2024)
Introduction: Teaching is a profession that requires dedication and knowledge, facing challenges such as devaluation and work overload. This study investigates the quality of life at work (QWL) of Early Childhood Education teachers in Pontal do Paraná, considering factors such as working conditions and professional recognition. Objective: To analyze how the teaching work impacts the quality of life of teachers, seeking to understand the realities of local institutions and identify unsatisfactory and satisfactory aspects in the work environment. Method: Descriptive and exploratory research, which applied the Total Quality Work Life questionnaire (TQWL-42) to assess QWL. The questionnaire was distributed electronically to 24 teachers, and data analysis was performed using the syntax SPSS and TQWL-42. Results: The results indicated an unsatisfactory level of quality of life, especially in the biological sphere, which includes physical and mental disposition, work capacity and health services. Excessive workload and lack of job stability were identified as critical factors. Most of the participants were female, facing double workdays. Conclusion: The research highlights the need to value the work of teachers, improving working conditions and health care. Aspects such as freedom of expression and autonomy are unsatisfactory, while job security is a positive point. Recognizing and supporting teachers is crucial, as they play a vital role in education and society, positively impacting the school environment and student development. DOI: https://doi.org/10.56238/sevened2024.037-101